Pelatihan Drama Berbasis Cerita Rakyat Bengkulu Sebagai Sarana Edukatif Bagi Anak Usia Dini di RT 14 Kelurahan Bumi Ayu Kota Bengkulu - Loliek Kania Atmaja; Indah Sartika; Septi Nurma Juwita (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Early childhood is in a golden age development phase that requires optimal stimulation to develop language skills, social-emotional abilities, creativity, and character values. However, learning activities in community settings are generally still dominated by conventional activities that provide limited opportunities for children to actively express themselves. In addition, Bengkulu folklore as part of local wisdom has not been optimally utilized as an educational medium in early childhood learning. This community service activity aims to improve language skills, self-confidence, creativity, cooperation, and understanding of cultural values through drama training based on Bengkulu folklore. The implementation method uses a Participatory Action Learning approach consisting of needs identification, socialization, training, mentoring, drama performance, and evaluation stages. The participants consisted of 25 children aged 5–6 years in RT 14, Bumi Ayu Subdistrict, Bengkulu City. The training materials included the introduction of Bengkulu folklore, vocal and expression exercises, movement and improvisation, role distribution, performance rehearsals, and evaluation. The results of the activity indicate improvements in speaking skills, confidence in performing in public, teamwork abilities, and understanding of local cultural values.